TIATR: Shaming, Humiliation, and the Dignity Project - Fernandes, Jason Keith (Archīum Ateneo, 2024)
Despite the popular acclaim and the sparse but enthusiastic academic attention that it has received, tiatr, the Konkani language theatrical tradition from Goa’s Old Conquests region, has battled a profound deprecation. It has consistently been dismissed as unsophisticated and “lacking in standard” and has regularly submitted to rigorous efforts to upgrade its standard. This essay locates this dismissal as the result of the shaming of working class and lower caste Catholics by those promoting British-Indian nationalist sensibilities, and examines the claim of humiliation by the tiatrist and activists promoting the rights of the largely Catholic communities using the Roman script for the language. In placing tiatr within the theoretical framework of humiliation studies led by Gopal Guru, the essay brings the question of caste, always lurking in the background of studies on Goa, but almost never effectively articulated, into the foreground. The essay demonstrates how caste is critical to understanding the development of tiatr and how the actions of the tiatrist and the Roman script activists are ways in which dignity is restored to Catholics in Goa from working caste and class locations.